ANTIOXIDANT ACTIVITY OF SOURSOP (ANNONA MURICATA L.) LEAF JELLY CONFECTIONS FORMULATED WITH MULTIPLE GEL MATRICES - Jumalia Aswar; Dewi Yuliana; Nasrul Haq; Zufiayu Sapiun; Abdul Rasyid, Faradiba (JURNAL KATALISATOR, 2025)
Jelly confections represent promising nutraceutical products by incorporating bioactive compounds with health-promoting properties. Soursop leaves (Annona muricata L.) are recognized as a potential source of antioxidant and antibacterial agents, yet their application in functional foods remains limited. This study evaluated the antioxidant activity of soursop leaf jelly confections prepared with different gel matrix combinations. Formulation optimization was carried out using three gel matrices, namely carrageenan: agar (9:6), carrageenan: konjac (5:1), and konjac: agar (7:3). Antioxidant activity was assessed by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay using a microplate reader spectrophotometer. The results demonstrated IC₅₀ values of 28.95 µg/mL for carrageenan: agar, 8.82 µg/mL for carrageenan: konjac, and 30.33 µg/mL for konjac: agar formulations. Among these, the carrageenan: konjac (5:1) formulation exhibited the most potent antioxidant activity, indicating its potential for developing functional jelly-based nutraceuticals.